2020
DOI: 10.1021/acsami.9b22338
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Highly Efficient Bilayer Photothermal Paper for Water Desalination and Purification: Self-Floating, Rapid Water Transport, and Localized Heat

Abstract: In view of the sustainable and environmentally friendly characteristics of solar energy, solar water evaporation has been identified as a promising approach to mitigate the global water crises. However, it is still a great challenge to develop a portable, flexible, scalable, and high-performance solar water evaporation material. Herein, a bilayer-structured solar water evaporation material consisting of a top multiwalled carbon nanotube (MWCNT) layer and a bottom polyphenylene sulfide/fibrillated cellulose (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…79 To the best of our knowledge, the reasons why cellulose-based paper has opportunities to become a supporting platform for solar absorbers for the construction solar evaporators can ascribe to the following points: (1) cellulose paper with high capillary power due to its microporous structure and excellent hydrophilicity can continuously pump water from the bulk to the interface, supporting the successful conversion of water to steam. 8,79 (2) Due to its low thermal conductivity and excellent thermal insulation, cellulose paper a as floater reduces the heat loss to the environment. 80 (3) The abundant functional groups on cellulose paper allow its modification with various photothermal materials for the construction of bilayer structures.…”
Section: Cellulose-based Papermentioning
confidence: 99%
See 3 more Smart Citations
“…79 To the best of our knowledge, the reasons why cellulose-based paper has opportunities to become a supporting platform for solar absorbers for the construction solar evaporators can ascribe to the following points: (1) cellulose paper with high capillary power due to its microporous structure and excellent hydrophilicity can continuously pump water from the bulk to the interface, supporting the successful conversion of water to steam. 8,79 (2) Due to its low thermal conductivity and excellent thermal insulation, cellulose paper a as floater reduces the heat loss to the environment. 80 (3) The abundant functional groups on cellulose paper allow its modification with various photothermal materials for the construction of bilayer structures.…”
Section: Cellulose-based Papermentioning
confidence: 99%
“…For example, multiwalled carbon nanotubes (MWCNTs) show remarkable solar absorbance over a wide spectrum range and a high light-to-heat conversion efficiency. 84 Huang et al 8 reported the preparation of a highly efficient bilayer photothermal paper by combining a top multiwalled carbon nanotube (MWCNT) layer and a bottom polyphenylene sulfide/fibrillated cellulose (PPS/FC) paper for water desalination and purification.…”
Section: Cellulose-based Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Steam generation was easily achieved by efficient harvesting of solar energy, which is viewed as a promising approach to obtain freshwater in these water‐stressed areas 5‐8 . Nevertheless, most of existing solar evaporation system is subjected to poor photo‐thermal conversion performance due to the heat dissipation to nonevaporating section by warming bulk water 9‐12 . Intentionally, confining heat to evaporation interface contributes to the escape of the interfacial water molecules from liquid to vapor, 13‐16 ultimately booming the evaporation performance.…”
Section: Introductionmentioning
confidence: 99%